SITUATION AND DEVELOPMENT PROSPECTS OF "ART TOURISM" IN UZBEKISTAN - Kholmurodova Shahnoza Ganisher qizi (American Journals, 2023)
This article analyzes the activity of art tourism as a new field of tourism research and its role in tourism and its impact on the economy. In analyzing this, we relied on the information of several art galleries in our country. Based on the received information, the potential of art tourism of our country was assessed and a model for the development of this field of tourism was presented. Based on the collected data, it was determined that the future development of this industry can be one of the main factors for increasing the tourism potential of our country through the method of forecasting the development of this tourism industry and its benefits.
Keywords: Art tourism, artist-tourist, art museum, art gallery